Diagnosis of primary cerebral lymphomas: possible value of PCR testing in equivocal cases requiring rebiopsy. (April 2014) - Shaw, Abigail; Iyer, Venkat; Rooney, Nick; Wragg, Rebecca; Waits, Paula; Roberts, Eileen; Haynes, Harry R.; Kurian, Kathreena M.
Abstract Introduction. Rebiopsy rates as high as 12% have been reported in previous studies of Primary Central Nervous System Lymphoma (PCNSL). This can lead to secondary operations, increasing risks of morbidity to the patient and costs for the NHS. Polymerase Chain Reaction (PCR) testing for clonality in haematological malignancies has been applied to cases of lymphoma outwith the central nervous system (CNS), but is less commonly used in the diagnosis of CNS lymphomas. Clonality in B- and T-cell populations may indicate the presence of malignancy. We aimed to identify factors to reduce the rebiopsy rate in PCNSL. Methods. We examined a cohort of 102 suspected cerebral lymphoma cases biopsied at Frenchay Hospital, Bristol over a 10-year period (2000–2010). Clinical data, including age, sex, location, pre-biopsy steroid use, the need for rebiopsy and histological diagnosis, were collected. We retrospectively reviewed rebiopsied cases and they subsequently underwent PCR testing for clonality. Results. Overall, 96/102 (94%) cases achieved a histological diagnosis after one or more biopsies. 81/96 (84%) of these were lymphomas involving the brain and 15/96 (16%) were spinal lymphomas. The majority of these were B-cell lymphomas (95/96 (99%)), with one case of peripheral T-cell lymphoma (1/96 (1%)). Due to insufficient histological evidence of PCNSL after the first biopsy, 9/102 (9%) of cases had required rebiopsy. In 7/9 (78%) of these cases, we undertook PCR testing for clonality on tissue from the first biopsy. We found 3/7 (43%) cases were monoclonal for B or T populations, raising the possibility of PCNSL. Conclusions. We recommend that all CNS lymphoproliferative lesions be assessed by haematopathologists, with the inclusion of PCR testing particularly in equivocal cases. This would reduce the number of patients going for rebiopsy and reduce the patient morbidity and costs for the NHS.